Service Convenience and Customer Patronage of Government Owned Hospitals in Abia State, Nigeria - Ezenta; Nneoma, Ogemdi; Osagie Leslie Uwabor, and (British Journal of Marketing Studies, 2020)
Healthcare service consumers (patients) make the choice of where to receive healthcare. They are very particular about the quality of services they receive. Service convenience is seen to be a great factor which entice and preserve customers. The study therefore, investigated the influence of service convenience on customer patronage of government owned hospitals (GOHs) in Abia State. The adaptation – level theory and the descriptive survey research design were adopted for the study. Three hundred copies of structured questionnaire were conveniently administered to adult patients who accessed the services of the general as well as specialist outpatients departments of the selected GOHs in Abia State. Frequency tables, simple percentages, and Kendal taub correlation were used to analyze data collected. The result revealed a positive significant relationship between service convenience and customer patronage of GOH in Abia State. Based on the result, we conclude that patients are satisfied with the services provided by the GOHs in Abia State. We therefore recommend, when hiring health personnel, managers should screen for knowledge competence and professional attitude.